Implementation of the TPACK Approach in Islamic Religious Education Learning at SMA Negeri Karanganyar - Saputro, Yogi Muhammad; Asmara, Linda; Fiddarain, Zaduna (Multicultural Islamic Education Review, 2025)
This research aims to describe and analyze the implementation of the Technological Pedagogical and Content Knowledge (TPACK) approach in Islamic Religious Education (PAI) learning at SMA Negeri Karanganyar. TPACK is a conceptual framework that combines three main components in modern learning, namely content mastery, pedagogical strategies, and the use of technology. In the context of PAI learning, the application of this approach is important to address the challenges of the digital era without losing the essence of religious values. This study uses a descriptive qualitative approach with data collection techniques in the form of observations, in-depth interviews, and documentation involving teachers, students, and learning materials. The research results show that the teachers' mastery of content knowledge is quite good, but the pedagogical and technological aspects have not been optimally integrated. The learning strategies are still conventional and teacher-centered, while the use of technology is limited to non-interactive visual presentation media. The Lesson Implementation Plan (RPP) does not yet reflect a systemic synergy between technology, pedagogy, and content. The obstacles faced include a lack of practice-based technical training, limited technological infrastructure, and cultural resistance to the digitalization of religious education. In conclusion, the implementation of TPACK in PAI learning at SMA Negeri Karanganyar is still in its early stages and requires strengthening in the aspects of planning, execution, and institutional support. Improvement strategies are needed in the form of structured training, provision of digital facilities, and reform of pedagogical culture to encourage more contextual, participatory, and adaptive PAI learning in the digital era.